Low-pressure Cu-Cu bonding using in-situ surface-modified microscale Cu particles for power device packaging. (15th July 2016) - Liu, Xiangdong; Nishikawa, Hiroshi
Abstract: An oxidation-reduction bonding (ORB) was applied to achieve Cu-Cu bonding with microscale Cu particle paste. During sintering at 300 °C, Cu2 O nanoparticles were homogeneously formed on the surface of the microscale Cu particles through a thermal oxidation, and were subsequently reduced to Cu nanotextured surface in formic acid atmosphere. This in-situ surface modification significantly enhances the sinterability of the microscale Cu particles, leading to a well-sintered microstructure and a three times higher bonding strength than that of the bonding joints prepared with non-oxidation bonding (NOB). Graphical abstract: